Associations of diabetes, circulating protein biomarkers, and risk of pancreatic cancer - Pang, Y; Lv, J; Wu, T; Yu, C; Guo, Y; Chen, Y; Chen, Z; Yang, L; Millwood, IY; Walters, RG; Yang, X; Stevens, R; et al. (Springer Nature, 2023)
Background: Type 2 diabetes (T2D) is associated with higher risk of pancreatic cancer (PC), but the underlying mechanisms are not fully understood. Methods: We conducted a case-subcohort study involving 610 PC cases and 623 subcohort participants with 92 protein biomarkers measured in baseline plasma samples. Genetically-instrumented T2D was derived using 86 single-nucleotide polymorphisms (SNPs), including insulin resistance (IR) SNPs. Results: In observational analyses of 623 subcohort participants (mean age, 52 years; 61% women), T2D was positively associated with 13 proteins (SD difference: IL6: 0.52 [0.23–0.81]; IL10: 0.41 [0.12–0.70]), of which 8 were nominally associated with incident PC. The 8 proteins potentially mediated 36.9% (18.7–75.0%) of the association between T2D and PC. In MR, no associations were observed for genetically-determined T2D with proteins, but there were positive associations of genetically-determined IR with IL6 and IL10 (SD difference: 1.23 [0.05–2.41] and 1.28 [0.31–2.24]). In two-sample MR, fasting insulin was associated with both IL6 and PC, but no association was observed between IL6 and PC. Conclusions: Proteomics were likely to explain the association between T2D and PC, but were not causal mediators. Elevated fasting insulin driven by insulin resistance might explain the associations of T2D, proteomics, and PC.